Epidemiologia das dermatofitoses em instituições públicas da região de Araraquara - SP - Baeza, L. C. [UNESP]; Rezende, J. F. [UNESP]; Silva, R. A. M. [UNESP]; Mirandci, E. T. [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (My University, 2004)
Dermatophytosis on skin, hair and nails are the most common infectious process in the world. A total of 94 individuals from Public Institutions from the city of Araraquara - Sao Paulo/Brazil, with suspected of dermatophytic lesions were examined in order to determine the incidence and etiology of dermatophytosis. 105 specimens were collected from August to December of 2001 in the Mycology Laboratory of the Faculdade de Ciências Farmacêuticas. It was observed that 47 samples were positive for dermatophytes. Trichophyton rubrum was the prevalent specie (59.6%), followed by Microsporum canis (17%), T. tonsurans (10.6%), T. mentagrophytes (8.5%) and Epidermophyton floccosum (4.3%). T. rubrum was the most frequent in interdigital lesions (81.5%) and M. canis was the main dermatophyte involved in scalp lesions (58.3%). Therefore, it was observed a predominance of antropophilic and zoophilic species, respectively. These results are in agreement with statistical data from South and Southeast regions of Brazil, as well as from other parts of the world in which these fungi were the most frequently isolates from tinea pedis and tinea capitis. In this study, it was also observed a high percentage of T. tonsurans (41.7%) in tinea capitis and this result was different from the statistical data collected until now in our region.
Epidemiology of the dermatophytosis in public intitutions of the region of Araraquara city - SP
Keywords: Dermatophytes; Dermatophytosis; Epidemiology; Brazil; controlled study; dermatomycosis; dermatophyte; Epidermophyton floccosum; fungus isolation; human; incidence; information processing; Microsporum canis; mycology; nonhuman; prevalence; sanitation; skin disease; statistical analysis; tinea capitis; tinea pedis; Trichophyton mentagrophytes; Trichophyton rubrum; Trichophyton tonsurans